High-dose intravitreal chemotherapy in the treatment of high-risk retinoblastoma (Ukrainian Journal of Ophthalmology, 2025)
Background: Intravitreal chemotherapy (IVitC; intravitreal cytostatic injections) is the most promising field of multiagent chemotherapy for retinoblastoma, and, when combined with systemic multiagent chemotherapy, enables maximum effects on the tumor.Purpose: To improve the method of primary combination multiagent chemotherapy by increasing the melphalan dose and shortening the interval between the first and last injections in IVitC for high-risk retinoblastoma.Material and Methods: As per the improved methodology, melphalan was intravitreally injected at a dose of 20 or 30 µg in 0.1 ml, depending on the type of tumor and type of vitreous seeds, with the interval between intravitreal injections shortened to 10-11 days. The treatment method proposed was used in 8 eyes with a large high-risk tumor (7 eyes with a T3 tumor and one eye with a T2 tumor) in 7 patients aged 42 ± 4.1 months (range, 2 to 60 months).Conclusion: We have developed a method of treatment for high-risk T3 retinoblastomas with or without vitreous seeds which involves local chemotherapy at an increased dose of 20 µg or 30 µg every 10 to 14 days, in the presence of combination multiagent chemotherapy incorporating systemic multiagent chemotherapy, chemoreduction, every three weeks.  Our clinical studies demonstrated that the use of the method proposed resulted in tumor size reduction, tumor density increase and tumor calcification, with necrotic changes in vitreous seeds in eyes poorly responsive to the standard intravitreal dose of 10 µg melphalan in 0.1 ml diluent. The major indications for an increase in intravitreal melphalan dose to 20 µg are large T2 or T3 tumors located in the macular or juxtpapillary retina, with loss of tumor capsule integrity, dust vitreous seeds or cloud vitreous seeds. In addition, in the absence of parental consent for enucleation, an intravitreal melphalan dose can be increased to 30 µg as an alternative to enucleation for large T3 tumors with tumor capsule rupture, release of tumor fragments into the vitreous, spherical vitreous seeds, and blindness with no potential for vision restoration.
Keywords: retinoblastoma; intravitreal chemotherapy; combination chemotherapy; children